The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12072-011-9309-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between acetylator phenotype and genotype polymorphism of n-acetyltransferase-2 in tuberculosis patients

Abstract: This study suggests that the acetylator status of TB patients can be detected by phenotypic method as efficaciously as by genotypic method. Therefore, phenotypic method can replace genotypic method to determine acetylating status as phenotypic method is simple and inexpensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…, Rana et al . and Rana et al . were excluded due to overlap with their other studies (we therefore selected the later publication to analyse the distribution of the NAT2 genotype); three studies, by Guaoua et al .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…, Rana et al . and Rana et al . were excluded due to overlap with their other studies (we therefore selected the later publication to analyse the distribution of the NAT2 genotype); three studies, by Guaoua et al .…”
Section: Resultsmentioning
confidence: 90%
“…The main characteristics of the 37 studies are shown in Table 1. The studies by An et al [15], Rana et al [16] and Rana et al [17] were excluded due to overlap with their other studies (we therefore selected the later publication to analyse the distribution of the NAT2 genotype); three studies, by Guaoua et al [18], Ng [19] and Mishra et al [20], were excluded as controls were not TB patients but healthy people; the studies by Roy et al [21] and Cavaco et al [22] were excluded due to the absence of complete NAT2 polymorphism distribution data. The study by Ohno et al [23] was excluded due to the absence of slow acetylators.…”
Section: Identification and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…We contacted several study authors for clarification. For two articles,51,68 we did not receive a response and, consequently, data from the older article68 were excluded from a meta-analysis to which both articles contributed data. If the two articles reported data for two distinct cohorts, then information would have been lost by excluding one article.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the differences in the NAT2 slow‐acetylator allele frequencies were not statistically significant between cases and controls. In our previous study, we observed that the acetylator status of patients with TB can be detected by phenotypic method as efficaciously as by genotypic method. In the present study, we observed that NAT2 4/4, 4/5 and 4/7 alleles (fast acetylators) were not significantly different in ATT‐induced hepatotoxicity patients as compared to the non‐hepatotoxicity group, whereas NAT2 5/7 and 6/7 (slow acetylators) were significantly higher in hepatotoxicity patients as compared to the non‐hepatotoxicity group.…”
Section: Discussionmentioning
confidence: 99%